2012
DOI: 10.2109/jcersj2.120.138
|View full text |Cite
|
Sign up to set email alerts
|

Joining of alumina by using polycarbosilane and aluminum foil

Abstract: This paper describes a novel experiment in which alumina was joined using polycarbosilane (PCS) and an aluminum foil. PCS was used to design the surface structure of alumina, and the aluminum foil enabled the formation of an area that included the alumina surface designed using PCS; this area could be joined to ceramic materials. A four-point bending test revealed that the flexural strength of both the silicon carbide (SiC) and the silicon oxide (SiO 2 ) pieces that were obtained from alumina whose surfaces we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Thus, nonmetal interlayer needs to be developed to join ceramics to avoid the generation of the residual stress. The recent literature reported that alumina can be bonded well by ceramic interlayer [16][17][18][19][20][21][22] such as Al 2 O 3 and SiC. Particularly, B 2 O 3 was used to join alumina by transient liquid phase 23 forming whiskers in the joint.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nonmetal interlayer needs to be developed to join ceramics to avoid the generation of the residual stress. The recent literature reported that alumina can be bonded well by ceramic interlayer [16][17][18][19][20][21][22] such as Al 2 O 3 and SiC. Particularly, B 2 O 3 was used to join alumina by transient liquid phase 23 forming whiskers in the joint.…”
Section: Introductionmentioning
confidence: 99%